The Damage Caused to the Environment in the Context of the Sustainable Development of Society - Kudeikina, Inga; Kaija, Sandra (European Journal of Sustainable Development, 2019)
The opportunity to use the tangible resources of our planet – water, air, subterranean depths – secure the existence of our civilization. Despite the existence of private property and the division of ownership of tangible resources between natural and legal persons, the resources required for life are objectively determined by the very life form. Any living creature needs air, water and subterranean depths. They are the common value of the mankind. The right to live in a favourable environment is recognized as the basic right of each individual, of each member of the public. A significant aspect is the high quality environment, which includes specific standards and requirements for the quality of air, water and subterranean depths. This is necessary in order to ensure the legal protection of the environment, balancing the rights of private owners and society as a whole. The protection of the environment is the subject matter of the legal framework. The key challenge for the protection of the environment is to find an opportunity to balance the economic development and the sustainable development of the environment, which is why the greatest attention should be allocated to the questions that relate to the prevention and compensation for the damage caused to the environment. Keywords: environment, damage caused to the environment, sustainable development